(3Odjd EYOGO hJbjje OQGSGJ GdLOhi ddeTQhYGJ GdUfGYjI (B/s - (3NhGLcjI, eMeOs ((3YeGf(B: s (3ecJHI OGQ GdKbGaI(B, s, 2004)
(3eQGMd OhQI GdeTQhY,OQGSI GdLOhi GdEbJUGOjI hGdafjI,OQGSI GdShb,GNJjGQ GdJcfhdhLjG hgfOSIs
Keywords: (3GdeTQhYGJs; (3OQGSI GdLOhis